β-1,6-Glucan plays a central role in the structure and remodeling of the bilaminate fungal cell wall - Clara Bekirian; Isabel Valsecchi; Sophie Bachellier-Bassi; Cyril Scandola; J Inaki Guijarro; Murielle Chauvel; Thierry Mourer; Neil AR Gow; Vishu Kumar Aimanianda; Christophe d'Enfert; Thierry Fontaine (eLife)
The cell wall of human fungal pathogens plays critical roles as an architectural scaffold and as a target and modulator of the host immune response. Although the cell wall of the pathogenic yeast Candida albicans is intensively studied, one of the major fibrillar components in its cell wall, β-1,6-glucan, has been largely neglected. Here, we show that β-1,6-glucan is essential for bilayered cell wall organization, cell wall integrity, and filamentous growth. For the first time, we show that β-1,6-glucan production compensates the defect in mannan elongation in the outer layer of the cell wall. In addition, β-1,6-glucan dynamics are also coordinated by host environmental stimuli and stresses with wall remodeling, where the regulation of β-1,6-glucan structure and chain length is a crucial process. As we point out that β-1,6-glucan is exposed at the yeast surface and modulate immune response, β-1,6-glucan must be considered a key factor in host–pathogen interactions.